EVALUASI KEBIJAKAN PROGRAM REHABILITASI SOSIAL PENANGANAN GELANDANGAN DAN PENGEMIS PADA DINAS SOSIAL KOTA SERANG - Salman, Gibran Brilian; Bangsawan, Try Adhi; Saepudin , Eli Apud (Gapenas Publisher, 2025)
The issue of homelessness and begging continues to pose a significant social challenge, including in Serang City. To address this, the Serang City Social Affairs Office has implemented a Social Rehabilitation Program aimed at restoring the social functions of homeless individuals and beggars. This study evaluates the policy using William N. Dunn’s policy evaluation model, which includes six dimensions: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. A descriptive qualitative approach was employed, with data gathered through in-depth interviews, observations, and documentation involving social office staff, field officers, and program beneficiaries. The findings reveal that while the program has been relatively successful in reducing the recurrence of street begging, several obstacles remain, including limited budget allocation, lack of facilities, insufficient outreach, and a shortage of support staff. In conclusion, although the program demonstrates positive outcomes, improvements in supporting aspects are essential to ensure that the objectives of social rehabilitation are achieved more effectively and sustainably.